THE BENEFIT OF ADMINISTERING SEA GRAPE SIMPLICIA ON THE HISTOPATHOLOGICAL PICTURES OF WHITE RATS KIDNEYS GIVEN PARACETAMOL - Wijaya, Alvina Audria; I Ketut, Berata; Desak Nyoman, Dewi Indira Laksmi; Samsuri,; Merdana, I Made (Buletin Veteriner Udayana, 2025)
The use of paracetamol in high doses or over a long period of time can cause nephrotoxicity due to the accumulation of toxic metabolites. One of the natural ingredients that has the potential for protective effects against kidney damage is sea grapes (Caulerpa lentillifera), which are rich in antioxidant compounds. This study aims to evaluate the benefit of administering sea grape simplex on the histopathology of kidneys given paracetamol. This study used white rats (Rattus norvegicus) which were divided into five treatment groups, namely the negative control group (P0), the positive control group (P1) which was given 250mg/kgBW of paracetamol, and groups P2, P3, and P4 which were given paracetamol (250 mg/kgBW) with the addition of sea grape simplicia of 10 g/kgBW, 15 g/kgBW, and 20 g/kgBW respectively. After 14 days of treatment, the rat kidneys were taken and analyzed histopathologically using hematoxylin-eosin (HE) staining. The results of the study showed that group P1 experienced significant renal necrosis and congestion (P < 0.05) compared to P0. The treatment groups (P2, P3, and P4) showed a tendency towards decreased levels of necrosis and congestion, but were not statistically significantly different compared to P1 (P > 0.05). In conclusion, administration of sea grape simplicia at the doses used in this study did not provide a significant protective effect against paracetamol-induced nephrotoxicity. Further studies with higher doses and longer duration of administration are needed to explore its potential nephroprotective effects.